Representasi Setan Perempuan dalam Film Horor Indonesia Kontemporer: Studi Komparatif Pengabdi Setan (2017) dan Kuntilanak (2018) - Djazuli, Shafa Hamidah Aris (Jurnal Bahasa dan Sastra, 2026)
This study examines the representation of female demon figures in two Indonesian horror films, Pengabdi Setan (2017) and Kuntilanak (2018), from the perspectives of patriarchy, social construction, and the monstrous feminine. The study employs qualitative textual analysis by combining visual code analysis and narrative analysis on 24 purposively selected key scenes. The results show that the representation of female demons in both films is consistently built through recurring visual markers, including disheveled long hair, white or pale clothing, abnormal body posture, and their frequent appearance in domestic spaces. At the narrative level, both films position female figures within plot structures that culminate in expulsion or neutralization. Although the two films differ in the construction of backstory, Pengabdi Setan foregrounding domestic conflict and career-related causality, and Kuntilanak foregrounding maternal death under adverse social conditions, both ultimately direct the female supernatural figure toward a threatening role that must be resolved through elimination. These findings indicate that contemporary Indonesian horror continues to rely on gendered visual and narrative conventions in representing female supernatural figures. This study contributes to Indonesian popular culture and gender studies by offering an integrated comparative reading of visual and narrative patterns in two significant contemporary horror texts.